MODERN INDIAN SOCIETY: EDUCATIONAL AND SOCIAL PROBLEMS - Raulji, Anirudhdhasinh. Y. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Modern Indian society, with its rich historical heritage, has embarked on an adventurous journey where it is showing the ability to stand up to educational and social problems. In the context of these problems, we see that something is going wrong in the development of education and society, which is blocking the path to prosperity and harmony. Neglect of education is a big challenge, to face which we need to develop new approaches towards education. The level of education is low in most villages and small towns, due to which our children are deprived of countless opportunities. To solve this, we need to invest more in the field of education, increase the spread of education, and adopt new and simple measures to ensure quality. Social problems are also posing a big challenge in the development of our society. Problems like casteism and racial discrimination are causing great suffering to our society, which are becoming an obstacle in the path of prosperity and harmony. To overcome this, we need our society to work together to fight against casteism, fight more for equality in society, and provide facilities for the development of Dalits and tribes in particular. The solution to these problems can be found with the cooperation of all the members of the society, so that we can take the modern Indian society towards a new and prosperous future. It is very important to have our thinking and strong will to solve the problems in the field of education and society. Only when we overcome these problems together, we can build a prosperous and harmonious society. In this journey, our efforts and struggles will take us to new heights, which will lay the foundation for the prosperous future of our nation.